2005
DOI: 10.1111/j.1365-2389.2005.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Methane and nitrous oxide fluxes of soils in pure and mixed stands of European beech and Norway spruce

Abstract: Tree species can affect the sink and source strength of soils for atmospheric methane and nitrous oxide. Here we report soil methane (CH 4 ) and nitrous oxide (N 2 O) fluxes of adjacent pure and mixed stands of beech and spruce at Solling, Germany. Mean CH 4 uptake rates ranged between 18 and 48 mg C m ÿ2 hour ÿ1 during 2.5 years and were about twice as great in both mixed and the pure beech stand as in the pure spruce stand. CH 4 uptake was negatively correlated with the dry mass of the O horizon, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
64
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 30 publications
17
64
5
1
Order By: Relevance
“…This is in good agreement with previous observations (e.g. fluxes reported from several field measurements for temperate coniferous forests in Europe Borken et al, 2000Borken et al, , 2003Borken and Beese, 2006). However, consumption was lower than in some studies of temperate coniferous forests in North America (Yavitt et al, 1990;Castro et al, 1992;Gulledge et al, 2004).…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…This is in good agreement with previous observations (e.g. fluxes reported from several field measurements for temperate coniferous forests in Europe Borken et al, 2000Borken et al, , 2003Borken and Beese, 2006). However, consumption was lower than in some studies of temperate coniferous forests in North America (Yavitt et al, 1990;Castro et al, 1992;Gulledge et al, 2004).…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…CH 4 fluxes measured in this study correlated moderately with soil temperature but showed no strong relationship with soil moisture (not shown). Although volumetric soil water content of the soil is one crucial factor limiting CH 4 diffusion into soils (Wang et al, 2010(Wang et al, , 2005Borken and Beese, 2006;Chen et al, 2011a, b;Hartmann et al, 2011), Chen et al (2011a found that this is only valid for soil temperatures > 5 • C. Soil temperatures above 5 • C were only observed after snowmelt at our site (Fig. 2b).…”
Section: Seasonal Ghg Fluxesmentioning
confidence: 92%
“…These values were comparable to the estimated N 2 O emission from deciduous forest soils in Germany with an average of 0.37 kg N 2 O-N ha −1 yr −1 (SchulteBisping et al 2003). Studies have shown that emissions were smaller in coniferous stands than in broadleaf stands (Butterbach-Bahl et al 1998;Butterbach-Bahl et al 2002;Borken and Beese 2006), which were suggested to be caused by smaller gross rates of N mineralization and nitrification in coniferous than broadleaf stands (Ambus et al 2006). There is little information on the influence of different deciduous tree species on N 2 O emission.…”
Section: Gross Rates Of N Transformationmentioning
confidence: 99%